2007
DOI: 10.1111/j.1751-1097.2007.00212.x
|View full text |Cite
|
Sign up to set email alerts
|

Waveband and Dose Dependency of Sunlight‐induced Immunomodulation and Cellular Changes

Abstract: Both the UVB and UVA wavebands within sunlight are immunosuppressive. This article reviews the relationship between wavebands and dose in UV-induced immunosuppression mainly concentrating on responses in humans. It also contrasts the effects of UVB and UVA on cellular changes involved in immunosuppression. Over physiological sunlight doses to which humans can be exposed during routine daily living or recreational pursuits, both UVA and UVB suppress immunity. While there is a linear dose relationship with UVB c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
37
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 116 publications
0
37
0
Order By: Relevance
“…The dose of ssUV used (1.4 J/cm 2 ) would be delivered by 36 minutes exposure to sunlight in early spring in Sydney, Australia, at midday (0.64 mW cm 2 ). 33 Clearly, at more extreme times of year, such as mid summer or winter, shorter or longer exposure times would be required. Therefore, this dose is relatively low and achievable by natural sun exposure.…”
Section: Discussionmentioning
confidence: 99%
“…The dose of ssUV used (1.4 J/cm 2 ) would be delivered by 36 minutes exposure to sunlight in early spring in Sydney, Australia, at midday (0.64 mW cm 2 ). 33 Clearly, at more extreme times of year, such as mid summer or winter, shorter or longer exposure times would be required. Therefore, this dose is relatively low and achievable by natural sun exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that UVB radiation produces a variety of adverse effects that includes DNA damage [14,15], mutations in key regulatory genes [16], inflammation [17,18], immuno-suppression [19,20], photo-aging and skin cancer [21,22]. UVB is directly absorbed by cellular DNA leading to the formation of DNA lesions primarily cyclobutane pyrimidine dimers and pyrimidine (6-4)-pyrimidone photoproducts [13,23].…”
Section: Reactive Oxygen Speciesmentioning
confidence: 99%
“…Some of the hallmarks of this immunosuppression include UVB-induced genetic mutations in skin cells, circulation of cis-UCA from the isomerization of trans-UCA, production of reactive oxygen species (ROS), and generation of regulatory T and B cells that can transfer suppression into UVB-naïve mice. 3 Because UVB has both detrimental and beneficial effects on the immune system, it is critical to understand the mechanisms regulated by UVB so that effective prophylactic and palliative therapies can be designed for skin diseases, such as skin cancer, and immune-mediated diseases in internal organs, such as multiple sclerosis.…”
mentioning
confidence: 99%